2022
DOI: 10.3390/md20040235
|View full text |Cite
|
Sign up to set email alerts
|

5-O-(N-Boc-l-Alanine)-Renieramycin T Induces Cancer Stem Cell Apoptosis via Targeting Akt Signaling

Abstract: Cancer stem cells (CSCs) drive aggressiveness and metastasis by utilizing stem cell-related signals. In this study, 5-O-(N-Boc-l-alanine)-renieramycin T (OBA-RT) was demonstrated to suppress CSC signals and induce apoptosis. OBA-RT exerted cytotoxic effects with a half-maximal inhibitory concentration of approximately 7 µM and mediated apoptosis as detected by annexin V/propidium iodide using flow cytometry and nuclear staining assays. Mechanistically, OBA-RT exerted dual roles, activating p53-dependent apopto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 43 publications
(53 reference statements)
0
16
0
Order By: Relevance
“…Furthermore, a modified form of RT named 5- O -acetyl-renieramycin T eliminates lung CSCs and makes lung cancer cells more susceptible to cisplatin-mediated apoptosis [ 17 ]. 5- O -( N -Boc-l-alanine)-renieramycin T, another RT-modified compound, also binds and inhibits Akt function, resulting in apoptosis and cancer stem cell suppression [ 18 ]. A previous study of RT showed that this compound exerts apoptosis-induction effects by directly targeting Mcl-1, a key anti-apoptotic protein, and inducing its degradation through ubiquitin-proteasomal degradation [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, a modified form of RT named 5- O -acetyl-renieramycin T eliminates lung CSCs and makes lung cancer cells more susceptible to cisplatin-mediated apoptosis [ 17 ]. 5- O -( N -Boc-l-alanine)-renieramycin T, another RT-modified compound, also binds and inhibits Akt function, resulting in apoptosis and cancer stem cell suppression [ 18 ]. A previous study of RT showed that this compound exerts apoptosis-induction effects by directly targeting Mcl-1, a key anti-apoptotic protein, and inducing its degradation through ubiquitin-proteasomal degradation [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…GSK690693, an Akt inhibitor currently in phase I clinical trials, was reported to inhibit cancer cell proliferation and induce apoptosis in a subset of tumor cells with potency consistent with the intracellular inhibition of Akt kinase activity [ 45 ]. 5- O -(N-Boc-l-alanine)-renieramycin T and hydroquinone 5-O-cinnamoyl ester of renieramycin M, a series of renieramycin derivatives, showed CSC-suppression activities by inhibiting Akt signaling, resulting in the downregulation of CSC transcription factors (Nanog, Oct4, and Sox2) [ 18 , 32 ]. In this study, DH_25, a derivative of the RT right-half analog, efficiently inhibited and induced the death of lung CSCs ( Figure 4 A).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, APG115 can synergistically promote apoptosis of ibrutinib by promoting MCL-1 degradation 45,47,48 . The current potential application direction of APG115 is cooperating with cancer immunotherapy.…”
Section: Discussionmentioning
confidence: 99%